Reaction towards change of tax policy: single-tier tax system in Malaysia / Nur Syafiqah Hussin - Hussin, Nur Syafiqah (2015)
The introduction of single-tier tax system into Malaysian taxation system has caused the elimination of tax credit available to shareholders offered by the imputation tax system. Single-tier tax system was effectly implemented in January 1, 2008 that treats dividend income as exempted in the hands of the shareholders. However, the profound point under single tier tax system rest on the taxability of dividend income based on the company tax rate. Retirees, tax-exempt bodies and non-profit organisations that generally fall under lower tax bracket would feel the burden. This study, using 248 listed companies in Bursa Malaysia, specifically company with dividend paying status between year of 2002 to 2014, provides evidence on the effect of tax change on dividend payout to public listed companies in Malaysia. The study found no statistically difference in the mean score of dividend payout before and after the implementation of single-tier tax system in Malaysia. From the perspective of dividend paying companies in Malaysia, the study also found a significant positive relationship between profitability and dividend payout, which means that companies in Malaysia distribute higher dividend payout when they record higher profitability. Lagged dividend also shows a significant positive relationship with dividend payout, which implies that companies in Malaysia are reluctant to cut their dividend payment to shareholders. In contrast, a significant negative relationship was found between growth opportunity and dividend payout, which indicates that companies in Malaysia tend to internally finance their expected investments faced by the company. As such, the theories supported for this study are information content/signalling theory, life cycle theory and agency theory. Nevertheless, liquidity and leverage were found not to have a significant relationship with dividend payout for companies in Malaysia.